Determination and Quantitative Comparison of Nucleosides in two Cordyceps by HPLC–ESI–MS-MS. (23rd February 2019) - Meng, Caifeng; Han, Qingjie; Wang, Xin; Liu, Xiaochen; Fan, Xueyan; Liu, Ruina; Wang, Qiao; Wang, Chunying
Abstract: A hybrid quadruple linear ion trap liquid chromatography-tandem mass spectrometry (LC–MS-MS) analytical method has been developed for simultaneous determination of 13 nucleosides from Cordyceps cicadae and Cordyceps sinensis for assessing whether C. cicadae can become a substitute for C. sinensis, based on that C. cicadae has in common with C. sinensis for treating chronic diseases. Among the 13 compounds, three compounds including cytidine, hypoxanthine and 2′-deoxyguanosine were firstly identified and quantified in C. cicadae . Ideal separation was achieved in one single LC–MS-MS run of 12 min by optimized chromatographic conditions. The identification and quantification analysis of target compounds were performed in electrospray ionization tandem mass spectrometry. The limit of detection and quantity for 13 compounds were <42.0 and 84.2 ng/mL, respectively. The determination results of 12 batches of C. sinensis and 20 batches of C. cicadae were then analyzed and classified by multivariate statistical analysis. C. cicadae contained a relatively higher level of three nucleosides (cytidine, uracil and 2′-deoxyuridine) than those in C. sinensis. The results of this study provided the theoretical basis for the substitution of C. sinensis with C. cicadae . The optimized method could be used for the quality control and investigate bioactive compound variation of Cordyceps .